2019
DOI: 10.2305/iucn.ch.2019.parks-25-2ss.en
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from 18 years of implementing the Management Effectiveness Tracking Tool (METT): A perspective from the METT developers and implementers

Abstract: Understanding the successes and failures of management of protected areas is vital for the conservation of global biodiversity. The Management Effectiveness Tracking Tool (METT) is a simple, questionnaire-based approach for assessing protected area management effectiveness (PAME). Since it was developed in 1999, it has become the most widely applied PAME tool, used in at least 127 countries worldwide. This paper reviews the development of the METT and how it has been implemented and adapted. A combination of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 17 publications
1
50
0
Order By: Relevance
“…Secondly, an understanding of the role of PAs in climate change adaptation processes has been steadily developing but there is much work to be done. For example, new questions to assess the effects of climate change on PAs have only recently been employed in Management Effectiveness Tracking Tool (METT) evaluations despite its long history and widespread use (Stolton & Dudley, 2016). Through investigation of change following an extreme event this study provides insights into similar considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, an understanding of the role of PAs in climate change adaptation processes has been steadily developing but there is much work to be done. For example, new questions to assess the effects of climate change on PAs have only recently been employed in Management Effectiveness Tracking Tool (METT) evaluations despite its long history and widespread use (Stolton & Dudley, 2016). Through investigation of change following an extreme event this study provides insights into similar considerations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the full and interim evaluation have also shown that the quality set and the evaluation process need to be revised and further developed. In the following, the main reasons for this in terms of content and process are listed [21,22] (for comparison, see [24,25]).…”
Section: Strengths and Weaknesses Of The Evaluation Methods And Processmentioning
confidence: 99%
“…Such approaches can be adapted to national requirements and contexts. Whilst not without their challenges (Cook and Hockings 2011;Mascia et al 2014) these methods have a long history and can, with training and support, be effective at capturing site-or PA network-level information (Fox et al 2014;Stolton et al 2019). While this information will often be most relevant at the site level, reporting might be more appropriate at the level of networks of sites or an entire country.…”
Section: Capturing Data On Effective Planning and Management To Cut Cmentioning
confidence: 99%